Micro Structure Analysis of the Ovaries of Common Carp, Cyprinus Carpio L. Inhabiting a Polluted Reservoir, Umiam in Meghalaya, India. (4th August 2014) - Massar, Bashida; Dey, Sudip; Dutta, Karabi
Abstract The study uses microscopy to analyze damage caused to the ovaries of a fresh water fish, Cyprinus carpio L., owing to its exposure to municipal wastes in a polluted reservoir, Umiam in Meghalaya, India. Histological analysis of the ovary showed atretic oocytes, detached ovarian wall, detached follicular linings, and necrosis of nuclei. Scanning electron microscopy revealed deformed oocytes with a rough and distorted surface. Transmission electron microscopy showed a poorly developed chorion, presence of relatively less electron-dense materials as compared with control, multinucleation in some cells surrounding the oocytes, and distorted and condensed mitochondria. The importance of microscopy in its different forms in analyzing histological, surface microstructural and fine structural damage to fish ovaries in response to environmental pollution owing to municipal wastes and city garbage is discussed with the help of available literature.